Decolonizing Knowledge Production: Barriers and Strategies for African Scholars in Academic Publishing - Ndanu Mutua, Sylvia (Multidisciplinary Journal of Technical University of Mombasa, 2025)
African researchers face significant challenges in academic publishing, including financial constraints, epistemic marginalization, linguistic biases, and reliance on informal support systems. These barriers hinder equitable participation in global knowledge production and perpetuate systemic inequalities. A qualitative phenomenological study involving 50 African intellectuals across disciplines explored these issues through semi-structured interviews. Thematic analysis revealed key obstacles, such as high article processing charges (APCs) and limited institutional funding, which hinder publication in high-impact journals. Linguistic biases favor English, disadvantaging non-native speakers, while peer review processes often exclude African perspectives, pressuring scholars to conform to Western epistemologies. Despite these hurdles, informal peer networks provide practical and emotional support, fostering resilience among African scholars. The findings underscore systemic inequities in academic publishing and the urgent need for inclusive reforms. Recommendations include decolonized knowledge production approaches that validate African epistemologies, ensure financial support, and promote linguistic inclusivity. Such measures would enable African researchers to share contextually relevant insights, enriching the global knowledge ecosystem. By addressing these disparities, the study contributes to advancing equality in academic publishing and strengthening efforts to decolonize scholarly communication. Enhanced inclusion of African scholars is essential for fostering diverse and equitable global scholarship.
Keywords: Academic Publishing; African Scholars; Decolonization; Epistemic Marginalization; Open Access Barriers